Fear influences phantom sound percepts in an anechoic room - Denys, Sam; Cima, Rilana F. F.; Fuller, Thomas E.; Ceresa, An-Sofie; Blockmans, Lauren; Vlaeyen, Johan W. S.; Verhaert, Nicolas (Frontiers in Psychology, 2022)
In an environment of absolute silence, researchers have found many of their participants to perceive tinnitus. With this between-subject experiment, we aimed to elaborate on these research findings, and investigated whether fear or level of perceived threat influences the incidence and perceptual qualities of phantom sound percepts (loudness and unpleasantness) in an anechoic room. We investigated the potential role of individual differences in anxiety, negative affect, noise sensitivity and subclinical hearing loss. In total, N = 78 normal-hearing volunteers participated in this study. Their hearing was evaluated, using gold-standard pure tone audiometry and a speech-in-noise test (Digit Triplet Test). Prior to a four-minute stay in an anechoic room, we randomized participants block design-wise in a threat and no-threat condition. Participants in the threat condition were deceived about their hearing and were led to believe that staying in the room would potentially harm their hearing. Participants were asked whether they perceived sounds during their stay in the room and rated the perceptual qualities of sound percepts. They were also asked to fill-out standardized questionnaires measuring anxiety (State-Trait Anxiety Inventory), affect (Positive and Negative Affect Schedule) and noise sensitivity (Weinstein Noise Sensitivity Scale). In line with published incidence rates, 74% of our participants reported having heard tinnitus-like sounds. Speech-in-noise identification ability was comparable for both groups of participants. The experimental manipulation of threat was effective, as indicated by significantly higher scores on a Threat Manipulation Checklist among participants in the threat condition as compared to those in the no-threat condition. Nevertheless, participants in the threat condition were as likely to report tinnitus percepts as participants in the no-threat condition, and tinnitus percepts were not rated as being louder or more unpleasant as a function of level of threat. For participants who did experience tinnitus percepts, a higher level of threat was associated with a higher degree of experienced unpleasantness. Higher negative affect was only slightly associated with higher ratings of tinnitus unpleasantness. The findings of our study are drawn from a rather homogenous participant pool in terms of age, gender, and educational background, challenging conclusions that are applicable for the general population.